Pemberitaan Isu Tsunami Megathurst 20 Meter Jawa dalam Tinjauan Jurnalisme Sains - Mia Reva Ukhtiana; Arief Subhan; Abdul Muis Sobri (Fidikom UIN Jakarta, 2022)
News coverage on natural disaster issues often appears from various academic, theological, and mystical perspectives. This article explores how the reporting model developed by Detik.com, Kompas.com, and pikiranrakyat.com in writing on the megathrust tsunami issue from the perspective of science journalism and how the three media's writing differs on this issue. This article uses the constructivist paradigm and the perspective of science journalism to see an overview of the practice of producing natural disaster issues in online media. The results show that the three online portals have succeeded in providing actual and factual information about natural disaster issues scientifically and, at the same time, increasing the reader's understanding of the early-warning system. Thus, this article illustrates that media should report disasters issues scientifically so the readers will think critically and empirically and support the change of disaster approach from curative to preventive.